Image processing for old movies by filters with motion detection - Skoneczny, Sławomir (Zielona Góra: Uniwersytet Zielonogórski)
Old movies suffer from various types of degradation: severe noise, blurred edges of objects (low contrast), scratches, spots,etc. Finding an efficient denoising method is one of the most important and one of the oldest problems in image sequenceprocessing. The crucial thing in image sequences is motion. If the motion is insignificant, then any motion noncompensatedmethod of filtering can be applied. However, if the noise is significant, then this approach gives most often unsatisfactoryresults. In order to increase the quality of frames, motion compensated filters are usually applied.
Keywords: image sequence filtering; motion detection